Economic consequences of the 1953 London Debt Agreement - Galofre-Vila, G; McKee, M; Meissner, C; Stuckler, D (Centre for Economic Policy Research, 2016)
In 1953, the Western Allied powers approved the London Debt Agreement, a radical plan to eliminate half of Germany’s external debt and create generous repayment conditions for the remainder. Using new data from the historical monthly reports of the Deutsche Bundesbank, this column argues that the agreement spurred economic growth by creating fiscal space for public investment, lowering costs of borrowing, and stabilising inflation.